2019
DOI: 10.1021/acsaem.9b01223
|View full text |Cite
|
Sign up to set email alerts
|

The Central Role of Ligand Conjugation for Properties of Coordination Complexes as Hole-Transport Materials in Perovskite Solar Cells

Abstract: Two zinc-based coordination complexes Y3 and Y4 have been synthesized and characterized, and their performance as hole-transport materials (HTMs) for perovskite solar cells (PSCs) has been investigated. The complex Y3 contains two separate ligands, and the molecular structure can be seen as a disconnected porphyrin ring. On the other hand, Y4 consists of a porphyrin core and therefore is a more extended conjugated system as compared to Y3. The optical and redox properties of the two different molecular complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…As shown in Figure a, the bare perovskite film surface shows a well-crystallized material with typical crystallite sizes of around 200–500 nm . After being coated with the reference HTL (Figure b), the perovskite surface is effectively coated, and the top surface is flat without visible pin holes.…”
Section: Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As shown in Figure a, the bare perovskite film surface shows a well-crystallized material with typical crystallite sizes of around 200–500 nm . After being coated with the reference HTL (Figure b), the perovskite surface is effectively coated, and the top surface is flat without visible pin holes.…”
Section: Results and Discussionmentioning
confidence: 95%
“…As shown in Figure 4 a, the bare perovskite film surface shows a well-crystallized material with typical crystallite sizes of around 200–500 nm. 22 After being coated with the reference HTL ( Figure 4 b), the perovskite surface is effectively coated, and the top surface is flat without visible pin holes. Replacing the dopant FK209 with (MeO-TPD)TFSI has no obvious influence on the film quality, as indicated in Figure 4 c to 4 g, where different doping levels of up to a 40% molar ratio were investigated.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is noteworthy that the conductivity of the more planar, conjugated molecule Y4 is remarkably higher than that of Y3. 133 As discussed in Section 2.5.2, an increased hole mobility of 1.0 Â 10 À3 cm 2 V À1 s À1 was reported for the sulfur-rich, organic HTM SMe-TATPyr. Interestingly, studies of this system revealed that the employment of an interfacial layer increased the PCE of SMe-TATPyr-treated perovskite solar cells from 20.4% to 22.3%.…”
Section: Dopant-free Pscs Built From Polymer Structures Containing Tpamentioning
confidence: 82%
“…The difference in the crystal packing of the non-planar vs. planar components in the two compounds is attributed to their different device properties. 133 A 5,10,15,20-tetrakis(4-[N,N-di(4-methoxyphenyl)amino phenyl])porphyrin was successfully prepared on a gram scale via the direct condensation of pyrrole and 4-[bis(4-methoxyphenyl)amino]benzaldehyde (Fig. 34a).…”
Section: Pscs Built From Metal Complexes Containing Tpamentioning
confidence: 99%
“…also demonstrated that PSCs with a mixture of Co II and Co III ‐based porphyrins as HTM could achieve an efficiency of 20.5 % with improved thermal stability [37] . Recent advances in HTMs based on porphyrin in high‐performance PSCs are summarized in Table S1 [38–47] …”
Section: Introductionmentioning
confidence: 96%